Using metaphor and art to talk about death with occupational therapy students - Guay, Manon; Mailloux, Élodie; Chagnon, Mathilde; Tremblay, Jessica; Boivin, Sarah-Maude; Bérard, Léanne; Tremblay, Catherine; Grondin, Andréane; Aylwin, Alexie; Lessard, Marjolie (Canadian Medical Education Journal, 2024)
Implication Statement Addressing the topic of death is essential to empower healthcare professionals to work with people, but there is a lack of training in this area. This study presents the perceptions of students and educators regarding the use of metaphor and artistic creation to explore values, prejudices, emotions, and experiential knowledge related to death. The pedagogical innovation allowed students to reflect on and express their perceptions of death, while also experiencing a listening posture, thereby contributing to the development of communication skills, among others.